Study on the new dynamics and driving factors of soil pH in the red soil, hilly region of South China - Shen, Yuye; Zhang, Zhongqi; Xue, Yue (Environmental monitoring and assessment, 2021)
Soil acidification has always been a substantial eco-environmental problem restricting agricultural development in the red soil region of southern China. It is necessary to determine the dynamic change in soil pH in this area to formulate regional agricultural and environmental management measures. Yujiang County, a typical county with red soil acidification in southern China, was selected as the study area. Based on soil data from 1982, 2007, and 2018, the spatiotemporal variation characteristics and the latest changes in soil pH in the county were analyzed. The results show that the soil pH in Yujiang County decreased from 5.66 to 4.74 and then increased to 4.96 from 1982 to 2018, showing a trend of first decreasing and then increasing. According to the spatial distribution characteristics of soil pH, the low soil pH values in the three periods were mainly distributed in the northern mountainous areas with more forestland and dry land area and some southern hilly areas, while the paddy soil pH values in the middle low hilly areas were relatively higher. The soil pH decreased rapidly from 1982 to 2007, showing a large area of acidification. In 2007, the proportions of acidic (4.5 < pH < 5.5) and strongly acidic (pH < 4.5) soils increased by 67.37% and 10.6%, respectively, compared with that in 1982. However, from 2007 to 2018, the soil pH of the whole county increased, and the acidification trend was alleviated, which is of great significance to the regional red soil ecological environment. Through the analysis of the main factors affecting the change in soil pH, it was found that the sharp decline in soil pH in Yujiang County during 1982–2007 was mainly caused by acid rain and excessive nitrogen application. From 2007 to 2018, no significant reduction in nitrogen fertilizer in this area occurred, and although the increase in soil organic matter contributed to alleviating soil acidification, the analysis showed that the decrease in acid rain was the main reason for the rise in soil pH in Yujiang County. At the same time, notably, there is a large area of soil in the area that is still acidic, and effective control of soil acidification is still an important ecological and environmental issue in this area. In order to further improve the pH value of soil in red soil region, it is suggested that on the basis of continuous improvement of acid rain, in addition to increasing soil organic matter by returning straw to field and other measures, appropriate amount of lime or alkaline biochar can be applied to better improve the soil ecological environment in red soil hilly region.